2021
DOI: 10.1111/1440-1630.12765
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the characteristics of occupation‐centred practice: A Delphi study

Abstract: Introduction Occupation‐centred practice is key to aligning with the contemporary paradigm. Benefits of this approach for clients and the profession are well documented, yet how to identify occupation‐centred practice is not yet understood. Therefore, this study aimed to uncover the characteristics of occupation‐centred practice and how they can be identified in practice. Methods A three round Delphi survey was conducted to gain consensus on the defining characteristics of occupation‐centred practice. Purposiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…A link to the profession through the use of a keyword (e.g., occupation, occupational therapy) will enable the profession to be promoted through the research that occupational therapists publish. Ford et al (2022) also reported there was a limited use of occupation related terminology in their scoping review. Inclusion of occupation related keywords in publications written by occupational therapists would enable occupational therapy research to be more easily discoverable and promoted amongst readers from outside the profession.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A link to the profession through the use of a keyword (e.g., occupation, occupational therapy) will enable the profession to be promoted through the research that occupational therapists publish. Ford et al (2022) also reported there was a limited use of occupation related terminology in their scoping review. Inclusion of occupation related keywords in publications written by occupational therapists would enable occupational therapy research to be more easily discoverable and promoted amongst readers from outside the profession.…”
Section: Discussionmentioning
confidence: 99%
“…The findings from this review, indicating that only a quarter of articles written by occupational therapists included occupational therapy related keywords is a concern if articles are to be associated with the field of occupational therapy. As the foundation of occupational therapy practice is engagement in occupation (Ford et al, 2022; Parnell & Wilding, 2010), occupational therapy research would be expected to be related to occupation or occupational therapy practice. Several authors have conducted bibliometric reviews of occupational therapy research by searching for words such as ‘occupational therapy’ (Brown et al, 2018; Brown et al, 2019; Torrecillas & Cruzado, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This finding was consistent with those of other authors (Di Tommaso et al, 2016). Other participants believed that occupation‐centred practice was the same as client‐centred practice, however, Ford et al (2022) showed that a therapist can be client‐centred but still use impairment‐based therapy. Furthermore, the use of inconsistent terminology to describe occupation‐centred practice by participants in this study aligns with other authors' assertion that occupational therapists can find describing their practice using profession‐specific terminology challenging and so they revert to biomedical and functional language (Murray et al, 2015; Wilding & Whiteford, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent Delphi study identified key features of occupation‐centred practice: underpinned by theory grounded in occupation, incorporating the client's context, using occupational language in professional discourse and documentation, and using occupation throughout the occupational therapy process (Ford et al, 2022). The advantages of occupation‐centred practice for clients, practitioners, and the occupational therapy profession include improved health outcomes, stronger professional identity, and role clarity (Molineux, 2011; Stav et al, 2012; Wilding & Whiteford, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Occupation-based interventions aim to enhance the performance of an individual when undertaking meaningful activities of daily living by increasing their social and community interaction [ 36 ]. Occupation-focused interventions encapsulate the rapid improvement of an individual’s performance through compensatory methods by implementing adaptive measures to be tailored to their current performance level [ 37 ]. Interventions are implemented to increase the performance of the individual in the desired or necessary tasks [ 38 ].…”
Section: Methodsmentioning
confidence: 99%